Research progress on the application of functional magnetic resonance imaging in cognitive dysfunction in patients with cerebral small vessel disease - Cao, Yingying; Lai, Zhenzhen; Wang, Jingwen; Ye, Bijun; Fan, Weiqiang; Ruan, Jiajia (Frontiers in Neurology, 2025)
Cerebral small vessel disease (CSVD) has recently garnered extensive attention owing to its significant disease burden, insidious onset, and the absence of effective specific treatments. Poor lifestyle habits and chronic diseases are closely linked to its occurrence and development, eventually resulting in cognitive dysfunction. Therefore, improvement of lifestyle, stable blood pressure, effective glucose lowering, low-salt and low-fat diet, smoking cessation, moderate exercise and adequate sleep are the keys to preventing cognitive dysfunction in cerebral small-vessel disease. Early prevention and intervention are of significant clinical importance and social value, particularly as CSVD represents a major contributor to cognitive dysfunction in approximately 40 million elderly individuals worldwide. This comprehensive review integrates findings across four functional MRI techniques—diffusion tensor imaging (DTI), resting-state functional MRI (rs-fMRI), magnetic resonance spectroscopy (MRS), and arterial spin labeling (ASL)—to provide a holistic framework connecting structural abnormalities with functional deficits in CSVD. This paper aimed to cover four aspects: an overview of CSVD, the correlation between the clinical manifestations of CSVD and cognitive dysfunction, the neuroradiological features of CSVD, and the application of functional magnetic resonance imaging (fMRI) in CSVD patients with cognitive dysfunction. The integration of these complementary techniques offers unprecedented insights into disease mechanisms, enabling improved early diagnosis, establishment of reliable imaging biomarkers for monitoring disease progression, and development of tailored therapeutic strategies to slow or prevent cognitive decline in affected individuals.